Use of fine needle aspirate from peripheral nerves of pure-neural leprosy for cytology and polymerase chain reaction to confirm the diagnosis: A follow-up study of 4 years - Abhishek De; Abu Hena Hasanoor Reja; Ishad Aggarwal; Sumit Sen; Amrita Sil; Basudev Bhattacharya; Nidhi Sharma; Asad Ansari; Aarti Sarda; Gobinda Chatterjee; Sudip Das (Wolters Kluwer Medknow Publications, 2017)
Background: Pure neural leprosy (PNL) still remains a diagnostic challenge because of the absence of sine qua non skin lesions of leprosy and a confirmatory diagnostic method. The authors had earlier described a simple yet objective technique of combining fine needle aspiration cytology (FNAC) coupled with a multiplex polymerase chain reaction (PCR) in a pilot study, wherein the technique showed promise of a reliable diagnostic tool. In the pursuit of further evidence, the authors carried out a 4-year study with PNL cases to find the efficacy and reliability of the said method in a larger sample size. Aim: This study was conducted to find the efficacy, reliability, and reproducibility of FNAC coupled with multiplex PCR and Ziehl-Neelsen (ZN) staining in identifying the cases of PNL. Materials and Methods: All cases that were suspected to be suffering from PNL, following evaluation by two independent observers were included in the study and were subjected to FNAC from the affected nerve, and the aspirates were evaluated for cytology, ZN staining, and multiplex PCR for Mycobacterium leprae genome. In addition, serum anti-PGL1 levels were also performed in all the study subjects. Fifteen non-PNL cases were also included in the control arm. Results: A total of 47 cases were included in the test arm and subjected to FNAC. Conventional ZN staining could demonstrate acid-fast bacilli (AFB) in only 15 out of 47 cases (31.91%) while M. leprae DNA could be elicited in 37 (78.72%) cases by the multiplex PCR. Only 13 (27.65%) out of 47 cases showed anti-PGLI-1 antibody positivity. On cytological examination of the nerve aspirates, only 11 (23.40%) cases showed epithelioid cells whereas nonspecific inflammation was seen in 26 (75.60%) cases. Conclusion: The results of this study conducted over a larger sample size corroborate with the findings of our pilot study. In a resource poor set up, FNAC in combination with ZN staining and multiplex PCR is a rapid, simple, and easily performed test, which can give a reproducible and objective diagnosis in cases of PNL.